Infectious and obstetric determinants of anemia among pregnant women in Southwest Ethiopia - Yosef, Tewodros; Gizachew, Asaye; Fetene, Gossa; Girma, Desalegn; Setegn, Melsew; Tesfaw, Aragaw; Sisay, Binyam Girma; Shifera, Nigusie (Frontiers in Global Women's Health, 2024)
BackgroundAnaemia, characterized by low red blood cell or haemoglobin levels, impairs oxygen transport in the body and poses a major global public health issue, particularly affecting pregnant women and children. This study focuses on identifying the factors contributing to anaemia among pregnant women receiving antenatal care (ANC) at Mizan-Tepi University Teaching Hospital (MTUTH) in southwest Ethiopia.MethodsA hospital-based unmatched case-control study was conducted from July 1 to August 30, 2022, involving 370 pregnant women (90 with anaemia and 280 without). Data collection included questionnaires, laboratory tests (Hgb and stool examination), and anthropometric measurements. SPSS version 21 was used for data analysis, with binary logistic regression identifying factors associated with anaemia. The significance level was set at a p-value <0.05.ResultsThe study achieved a 100% response rate for both cases and controls. Factors identified as determinants of anaemia among pregnant women included malaria infection (AOR = 7.83, 95% CI: 3.89–15.8), hookworm infection (AOR = 2.73, 95% CI: 1.39–5.34), short birth interval (AOR = 7.11, 95% CI: 3.59–14.2), and history of unsafe abortion (AOR = 5.40, 95% CI: 2.46–11.8).ConclusionThis study found that malaria infection, hookworm infection, birth interval <33 months, and a history of unsafe abortion are factors contributing to anaemia in pregnant women. Strategies such as distributing insecticide-treated bed nets (ITNs) to combat malaria, improving sanitation, anthelmintic drugs, promoting family planning to prevent unwanted pregnancies and unsafe abortions, and providing preconception care can help reduce the incidence of anaemia.